Respiratory rate monitoring in healthy volunteers by central photoplethysmography compared to capnography. Issue 4 (12th February 2022) - Henricson, Joakim; Glasin, Joakim; Rindebratt, Sandra; Wilhelms, Daniel
Abstract: Monitoring of respiration is a central task in clinical medicine, crucial to patient safety. Despite the uncontroversial role of altered respiratory frequency as an important sign of impending or manifest deterioration, reliable measurement methods are mostly lacking outside of intensive care units and operating theaters. Photoplethysmography targeting the central blood circulation in the sternum could offer accurate and inexpensive monitoring of respiration. Changes in blood flow related to the different parts of the respiratory cycle are used to identify the respiratory pattern. The aim of this observational study was to compare photoplethysmography at the sternum to standard capnography in healthy volunteers. Bland Altman analysis showed good agreement (bias −0.21, SD 1.6, 95% limits of agreement −3.4 to 2.9) in respiratory rate values. Photoplethysmography provided high‐quality measurements of respiratory rate comparable to capnographic measurements. This suggests that photoplethysmography may become a precise, cost‐effective alternative for respiratory monitoring. Abstract : An optical sensor probe is compared to a standard capnograph regarding measurement of respiratory rate. The optical sensor probe is applied to the sternum, using two red and two infrared light emitting diodes and four photo detectors capturing reflected light. Signal processing is based on integrated photoplethysmographic solution. The agreement (Bland Altman plot) between the optical sensor probe and the standard capnograph is very good.